A criação do inédito viável a partir do trabalho colaborativo de gestoras educacionais em um contexto virtual durante a pandemia da COVID-19 - Silva, Marli Pereira da (2022)
In March 2020, the world was hit by the coronavirus pandemic. The main measure to contain the disease was social distance, so classroom lessons were suspended and became remote. In this context, educational managers were affected by anxiety and insecurity regarding the actions to be taken. The Brincadas dos Gestores Educacionais – BGE (Educational Managers' Play Brigades) was created as a collaborative virtual space for reception, exchanges and possibilities of actions for managers of different school realities in São Paulo. This space became the context of this research, which aims to investigate the creation of the viable unheard from the collaborative work of educational managers in a virtual context during the COVID-19 pandemic in 2020. The theoretical foundation was based on the Cultural-historical Activity Theory – CHAT (VYGOTSKY, LURIA, LEONTIEV, 1934/2001; LEONTIEV, 1977; ENGESTRÖM, 1999; and LIBERALI, 2011), and on the concepts of Critical Collaboration (MAGALHÃES, 2011) and Viable Unheard (FREIRE, 1970/2011). Held over a period of five months, it totaled ten meetings and two Lives with seven managers: two from public schools and five from private schools. The data produced were collected through video recordings and transcribed for analysis. The research focused on discursive practices materialized in multimodal texts and in the principles of collaboration. The results indicated that the dramatic events resulting from extreme situations boosted the creation of viable unheard, listed here: the use of audio from the WhatsApp application for contacting families and students; virtual parties with the school community; the “Teacher's Life in the Pandemic”, a space for teachers to talk about their lives, concerns and talents; a Live to present good management practices in the pandemic; the memoir book “The bright side of the pandemic”, written by the students; cell phone donations from private school families to public school students; and the BGE itself, which offered emotional support, opportunities to share and connect with managers from other contexts through the feeling of empathy and union generated, for being “a breath of fresh air” and “a breath of hope”. The collaboration between the managers was evidenced by their prompt acceptance to participate in the group and by the negotiation of agendas and genuine interest in affective exchanges and experiences. The “viable unheard” creations were built collaboratively, based on the pillars of understanding differences, on the perception of complementarity and interdependence of the group. Despite divergent viewpoints and positions, relationships of trust, acceptance and tolerance remained grounded in common and collective goals. This dynamic generated emotional and cognitive strengthening necessary for the transformation of the socio-historical context and moment. We conclude that the participants built a comfortable collaboration environment, but they stood out in their co-created actions to overcome the drama of the school context situations generated by the pandemic. The research contributes to the historical understanding of management practices during the pandemic and expands to future studies in the direction of creating the viable unheard, for critical analysis of the crisis, for new possibilities of transforming oneself and the school context